Research on wave regimes at the Cua Dai estuary, Quang Nam - Dinh, Cham Dao; Lai, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2020)
In coastal area of the Cua Dai estuary - Quang Nam province, the processes of erosion-accretion strongly occur. Over this area, the ocean wave is a dynamical factor that directly affects the coastal areas causing erosion-accretion processes. This paper presents an evaluation of the ocean wave regime impacting the areas of Cua Dai estuary by using the model of MIKE21SW. The purpose of this study is to fully interprete the role of dynamical factor, ocean wave in erosion-accretion processes. The results showed a convergence of ocean waves at the estuary of Cua Dai although it is obstructed by the Cu Lao Cham island in front of the Cua Dai estuary. The northeast and north-northeast waves are mainly prevailing with the frequency of more than 60% in the year.